Effect of Separating-Area between Apartments on the Speed of Fire Spread in High Rise Residential Buildings (The International Journal for Scientific Research, 2023)
Fire accidents in high-rise residential buildings lead to great loss of life and property and constitute a serious threat to the difficulty of safe evacuation due to the presence of various flammable materials and high population density, so there are great challenges facing architects and specialists in order to improve and develop design methods to protect from fire and reduce losses. The space separating apartments can be a factor influencing the spread of fire, its development, and the speed of its transmission in tall residential buildings. To clarify this, the spread of fire was followed vertically and systematically by simulating the characteristics of fire spread for a 12-story building using the pyrosim program. The simulation results showed that the risk of fire spreading in tall residential buildings increases with the space separating apartments and that the effect of the depth of space is more obvious the greater the width of the space separating apartments. For separating spaces, and thus the research can contribute to choosing the optimal design to increase the chance of safe evacuation in the event of a fire in high-rise residential buildings.
Keywords: High rise buildings; Separation area; Pyrosim; Fire spread